2020
DOI: 10.1002/mma.6897
|View full text |Cite
|
Sign up to set email alerts
|

Invariants of BT[p,q], BT(X)[p,q] and BT(Y)[p,q]

Abstract: Boron nitride nanotubes (BNNTs) have been increasingly investigated for use in a wide range of applications due to their unique physicochemical properties including high hydrophobicity, heat and electrical insulation, resistance to oxidation, and hydrogen storage capacity. They are also valued for their possible medical and biomedical applications including drug delivery, use in biomaterials, and neutron capture therapy. Chemical graph theory provides different tools to investigate different properties of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 14 publications
1
38
0
2
Order By: Relevance
“…All this information can be considered as a subset of Figure 3B in this paper, indicating that more samples are needed to obtain a more comprehensive understanding. Recently, Huang et al (2020) pointed out that the optimal temperature for COVID-19 spread was 5∼15 • C, and 70% of confirmed cases worldwide occurred between 5 and ∼15 • C, which is similar to this paper. In addition to Hubei Province, China still has 58.2% of cases in this temperature range, but only 43.2% of the temperature data (Figure 3A).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All this information can be considered as a subset of Figure 3B in this paper, indicating that more samples are needed to obtain a more comprehensive understanding. Recently, Huang et al (2020) pointed out that the optimal temperature for COVID-19 spread was 5∼15 • C, and 70% of confirmed cases worldwide occurred between 5 and ∼15 • C, which is similar to this paper. In addition to Hubei Province, China still has 58.2% of cases in this temperature range, but only 43.2% of the temperature data (Figure 3A).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Ma et al (2020) and Wang et al (2020) have shown that temperature changes and humidity may be important factors affecting the spread of COVID-19 and mortality in COVID-19 patients. Recently, Huang et al (2020) pointed out that optimal air temperature for COVID-19 transmission is 5∼15 • C in many countries and regions in the world, and they considered the impacts of meteorological factors in the epidemic model and developed the world's first global prediction model for COVID-19 (http://covid-19.lzu.edu. cn/).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the MgO and MgO@Na 2 O nanoparticles had relative weight losses of 17 and 7 %, respectively. The weight loss of the catalysts in the second stage can be effected by the complete evaporation of water from their layers, completely eliminating the existing Mg(OH) 2 in the catalyst structure and changing to MgO 34. Significant weight reduction was observed in the samples by increasing the temperature from 800 to 1000 °C, and the MgO and MgO@Na 2 O catalysts had about 20 and 10 % weight loss in the whole TGA process, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A single trapezoid-shaped antenna in place of the discrete antenna array might be used to facilitate the fabrication of the delicate device structure. [15][16][17][18][19] The scheme capitalizing on such a single antenna is expected to provide an enhanced phase gradient over a wide band, thereby rendering broadband anomalous reflection. For the supercell with a superwavelength lattice period, the angle of anomalous reflection is simply determined by the modified diffraction equation.…”
mentioning
confidence: 99%
“…17 Unlike conventional blazed gratings, which tap into a sawtooth échelette profile to exhibit a maximum diffraction efficiency at a specific wavelength, the anomalous reflection is efficiently achieved throughout a broad band for the planar metasurface. 15,16 It is noted that due to the inherent shape of the antenna, the enhanced anomalous reflection is polarization-dependent and therefore the metasurface can be potentially treated as a broadband polarization beam splitter, 15 which might not be easily fulfilled using a diffraction grating. 20 Despite its vulnerability to dissipative optical loss, a plasmonic metasurface is deemed to give rise to an appreciable level of anomalous reflection beyond 80%, which can readily be applied to spectroscopy, imaging, and photovoltaics.…”
mentioning
confidence: 99%